Synthesis and characterization of a near-infrared persistent luminescent Cr-doped zinc gallate–calcium phosphate composite. Issue 35 (30th August 2022) - Shiu, Wai-Tung; Chang, Lo-Yueh; Jiang, Yingying; Shakouri, Mohsen; Wu, Yu-Hao; Lin, Bi-Hsuan; Liu, Lijia
Abstract : A new near-infrared-emitting persistent luminescent nanocomposite is synthesized and is luminescence mechanism is discussed. Abstract : Near-infrared (NIR)-emitting persistent luminescence (PersL) nanoparticles have attracted great attention as a novel optical probe for bioimaging and biosensing applications. These nanoparticles emit long-lasting luminescence after the removal of the excitation source, which effectively eliminates the interference from tissue autofluorescence. Cr-doped zinc gallate (ZnGa2 O4 :Cr 3+, CZGO) is a representative NIR-emitting PersL material. On the other hand, amorphous calcium phosphate (ACP) is a widely used drug carrier due to its high biocompatibility. In this work, we present a design of an ACP-based drug carrier with PersL properties, by forming a CZGO–ACP composite. The PersL properties of CZGO were preserved by composite formation, while it is found that the Zn 2+ could migrate from CZGO to ACP during composite formation, leading to different luminescence mechanisms between pure CZGO and the CZGO–ACP composite. The electronic structure of the composite was analyzed by synchrotron X-ray absorption spectroscopy, and a structure–luminescence correlation was proposed.